Blending Formal and Informal Learning Networks for Online Learning - Czerkawski, Betül C. (International Review of Research in Open and Distributed Learning, 2016)
With the emergence of social software and the advance of web-based technologies, online learning networks provide invaluable opportunities for learning, whether formal or informal. Unlike top-down, instructor-centered, and carefully planned formal learning settings, informal learning networks offer more bottom-up, student-centered participatory but somewhat disorganized learning opportunities for students. This paper presents a research study where graduate students are surveyed in their use of informal and formal learning networks in online courses to understand the interaction between the two and how they impact each other. The findings showed that students and professors use both environments often, to optimize learning but online course design is usually not designed to consider informal experiences of the students. The results and illustrated course design framework may contribute to the discussion of blending informal and formal learning for online learning.